POTENSI JENIS TUMBUHAN DI PULAU MALAWA DESA WAESALA KECAMATAN HUAMUAL BELAKANG, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Valentino Jusuf Ukru; Andjela Sahupala; Cornelia M. A. Wattimena (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Malawa Island is a small island that possesses a diversity of plant species with significant potential in maintaining the stability of coastal ecosystems. This study aimed to determine the potential of plant species on Malawa Island, Waesala Village, Huamual Belakang District, West Seram Regency. The research was conducted from March to April 2025 using a descriptive exploratory method through field surveys. Data collection was carried out using systematic transect methods and observation plots measuring 20 × 20 m. Plant observations were conducted based on morphological characteristics, determination keys, and taxonomic literature. The results showed that 66 plant species were found on Malawa Island, consisting of 6 species of Pteridophyta and 60 species of Tracheophyta, with the dominance of the Magnoliopsida class. The ecological conditions of the study area were characterized by high light intensity, average salinity of 33 ppt, average temperature of 34.33°C, humidity of 71%, and sandy coastal substrate. The diversity of species found indicates that the vegetation of Malawa Island is still relatively well preserved and has important potential in maintaining the stability of coastal ecosystems, reducing coastal abrasion, and supporting environmental sustainability.